Applications of Ultrasonography in Buffalo Reproduction - Karshanbhai Chaudhari, Ravjibhai; Virabhai Sutaria, Tarunkumar; Fuljibhai Chaudhari, Chandrakant (The Indian Journal of Animal Reproduction, 2026)
Ultrasonography has emerged as a transformative tool in buffalo reproduction, offering non-invasive, real-time insights into the anatomical and physiological aspects of the reproductive tract. In addition to its routine application for preg nancy diagnosis, ultrasonography is crucial for monitoring fetal development, diagnosing fetal anomalies, and identify ing conceptus loss. This helps in timely interventions by diagnosing non-pregnant animals or those having pregnancy issues, which can significantly improve reproductive outcomes. The ability of ultrasonography to enhance our under standing of follicular dynamics in buffaloes has significantly improved fertility management practices. By closely moni toring follicle development and ovulation timing, veterinary professionals can optimize breeding schedules and improve the success rates of artificial insemination. The combination of high-resolution B-mode imaging and Doppler modal ities aids in predicting fertility outcomes in various obstetrical conditions such as uterine torsion. Clinicians can make informed decisions regarding treatment options and prognosis by assessing blood flow to the reproductive organs and evaluating the uterine health. This review emphasises the routine application of ultrasonography for pregnancy diagnosis and the identification of reproductive disorders, while also exploring its advanced use in obstetrics, assisted reproductive technology, and male reproduction. As this technology continues to evolve, it promises to play an increasingly vital role in advancing buffalo reproduction.
Keywords: Buffalo; Pregnancy diagnosis; Infertility; Uterine torsion; Ultrasonography